Pangenome analysis reveals yield- and fiber-related diversity and interspecific gene flow in Gossypium barbadense L. - Qingying Meng; Peihao Xie; Zhongping Xu; Jiwei Tang; Liuyang Hui; Jiaqi Gu; Xinxin Gu; Shihe Jiang; Yuxuan Rong; Jie Zhang; Joshua A. Udall; Corrinne E. Grover; et al. (Nature Communications)
Abstract Gossypium barbadense is renowned for its superior fiber quality, particularly its extra-long fibers, although its fiber yield is lower compared to G. hirsutum. Here, to further reveal fiber-related genomic variants of G. barbadense, we de novo assemble 12 genomes of G. barbadense that span the wild-to-domesticated continuum, and construct a graph-based pangenome by integrating these assemblies and 17 publicly available tetraploid cotton genome assemblies. We uncover the divergent evolutionary trajectories and subsequent exchanges between G. barbadense and G. hirsutum through investigation of structural variants (SVs). We perform the SV-based GWAS analysis in G. barbadense and identify four, three, and seven candidate SVs for fiber length, fiber strength, and lint percentage, respectively. Furthermore, we detect the underlying candidate genes and uncover the origin and distribution of favorable alleles, and reveal the tradeoff between lint percentage and fiber quality. These pangenome and trait-associated SVs provide insights into and resources for improving cotton fiber.